Studi Adsorpsi Larutan Gliserol Menggunakan Karbon Aktif: Efek Konsentrasi, Tegangan Permukaan Dan Temperatur - Yuniawan Hidayat; Atmanto Heru Wibowo; Dwi Ngandayani (EKSAKTA: Journal of Sciences and Data Analysis, 2011)
The effect of adsorbate concentration, surface tension and temperature on glycerol adsorption  over  activated  carbon  have  been  conducted.  Activity  of  adsorbent  was increased  by  soaking  activated  carbon  in  H2SO4  10%  solution  for  12  hours  followed heating  at  a  temperature  of  500oC  under  N2  gas  flow  for  3  hours.  Furthermore,  the identification  and  characterization  of  activated  carbon  were  done  by  infrared spectroscopy  (IR)    and  gravimetric  method  acidity  test.  Conditions  of  adsorption  of glycerol  by  activated  carbon  were  carried  out  using  batch  method  with  ±12  hours  of contact time on the variation of adsorbate concentration or the ratio glycerol : water (v/v) 1 : 2, 1 : 3, 1 : 4, and 1 : 5, as well as variations in 30, 40, 50, and 60 oC.  The  result  showed  that  increased  activity  of  activated  carbon  increased  acidity from 0.5 mmol/gram  to 2.7 mmol/gram.  Increasing concentration of glycerol causes  the surface  tension  decreases  and  (∂γ/∂C)  becomes  negative with means  that  glycerol was adsorbed  over  the  surface.  It  has  been  confirmed  by  the  increase  of  actvated  carbon capacity is proportional to the increased concentration of glycerol. Temperature was also playing the role of glycerol adsorption where at 60 oC maximum adsorption was riched.   Keywords:  Adsorption,  Glycerol,  Adsorbate  concentration, Temperature,  Surface tension, Activated Carbon